Relationship between chorioamnionitis or funisitis and lung injury among preterm infants: meta-analysis involved 16 observational studies with 68,397 participants - Wen-li Liu; Yao Zhou; Chao Zhang; Jun Chen; Xu-feng Yin; Feng-xia Zhou; Shao-jun Chen (BMC, 2024)
Abstract Background Chorioamnionitis (CA) can cause multiple organ injuries in premature neonates, particularly to the lungs. Different opinions exist regarding the impact of intrauterine inflammation on neonatal respiratory distress syndrome (NRDS) and bronchopulmonary dysplasia (BPD). We aim to systematically review the relationship between CA or Funisitis (FV) and lung injury among preterm infants. Methods We electronically searched PubMed, EMbase, the Cochrane library, CNKI, and CMB for cohort studies from their inception to March 15, 2023. Two reviewers independently screened literature, gathered data, and did NOS scale of included studies. The meta-analysis was performed using RevMan 5.3. Results Sixteen observational studies including 68,397 patients were collected. Meta-analysis showed CA or FV increased the lung injury risk (OR = 1.43, 95%CI: 1.06-1.92). Except for histological chorioamnionitis (HCA) (OR = 0.72, 95%CI: 0.57-0.90), neither clinical chorioamnionitis (CCA) (OR = 1.86, 95%CI: 0.93-3.72) nor FV (OR = 1.23, 95%CI: 0.48-3.15) nor HCA with FV (OR = 1.85, 95%CI: 0.15-22.63) had statistical significance in NRDS incidence. As a result of stratification by grade of HCA, HCA (II) has a significant association with decreased incidence of NRDS (OR = 0.48, 95%CI: 0.35-0.65). In terms of BPD, there is a positive correlation between BPD and CA/FV (CA: OR = 3.18, 95%CI: 1.68-6.03; FV: OR = 6.36, 95%CI: 2.45-16.52). Among CA, HCA was positively associated with BPD (OR = 2.70, 95%CI: 2.38-3.07), whereas CCA was not associated with BPD (OR = 2.77, 95%CI: 0.68-11.21). HCA and moderate to severe BPD (OR = 25.38, 95%CI: 7.13-90.32) showed a positive correlation, while mild BPD (OR = 2.29, 95%CI: 0.99-5.31) did not. Conclusion Currently, evidence suggests that CA or FV increases the lung injury incidence in premature infants. For different types of CA and FV, HCA can increase the incidence of BPD while decreasing the incidence of NRDS. And this "protective effect" only applies to infants under 32 weeks of age. Regarding lung injury severity, only moderate to severe cases of BPD were positively correlated with CA.